Conducta obstétrica en el manejo del sangrado uterino anormal en adolescente de 11 años. - Segura Zatizabal, Elías Daniel (2023)
Abnormal uterine bleeding frequently occurs in the first years of gynecological life, generally due to the immaturity of the hypothalamic-pituitary-ovarian axis, which can lead to hormonal imbalances and irregular menstrual cycles. The objective of this study is to interpret the obstetric conduct to be followed in the management of abnormal uterine bleeding in eleven-year-old adolescents, to assess the effectiveness of the treatment. A retrospective review of the patient’s medical history was carried out, investigating the clinical, diagnostic and evolutionary characteristics during the period of hospital stay and the aim was to verify the effectiveness of hormonal therapy based on combined oral contraceptives in the treatment of dysfunctional uterine bleeding in adolescents.